Accelerating Africa’s climate action agenda through supporting soil health - Accelerating Impacts of CGIAR Climate Research for Africa; African Union Commission Sustainable Environment and Blue Economy Directorate (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Earth’s soils are a vast reservoir of carbon, holding approximately 2,400 - 2,500 gigatons (Gt) of carbon. This amount surpasses the carbon content found in the atmosphere by more than threefold and exceeds the combined amount stored in all living plants and animals by fourfold.